HUBUNGAN DUKUNGAN KELUARGA DENGAN PENGOBATAN KANKER SERVIKS DI RSUD Dr.H. ABDUL MOELOEK PROVINSI LAMPUNG - Desi Ari Madi Yanti (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Health is a stase off well being of body, soul and social that allows every productive socially and economically. Cervical cancer is a scourge for women for cervical cancer in the organ attacked the women, the cause of cervical cancer are surgery, chemotherapy and radiotherapy. The purpose of this study was to determine the relationship of family support with cervical cancer treatment in hospital Dr.Abdul Moeloek Bandar Lampung. This study used cross sectional design. Sampling technique total sampling with a number of 67 respondents. Statistical analysis using Chi-Square. The results of the bivariat analysis no family support relationship with cervical cancer treatment in hospital Dr.H.Abdul Moeleok Bandar Lampung in 2016 ( P-value 0.008 ). It is hoped to health workers to conduct health education to the respondent about the importance of family support for treatment of cervical cancer.